THE ROLE OF RELIGIUSITY IN REDUCE EMPLOYEE'S WORK STRESS - Fikri Fikri; Lusy Marianti; Ahmad Hidayat (Psikoislamedia : Jurnal Psikologi, 2023)
Stress is a condition of psychological and biological tension that exists in employees due to the large amount of work pressure, the result of stress will affect the health, emotions, thought processes and work productivity of employees. Based on previous research, one of the efforts to reduce work stress is to increase employee religiosity. Religiosity is a complex integrity between religious knowledge, feelings and religious actions in a person. The purpose of this study was to determine the extent to which religiosity influences the work stress. Data collection methods in this study used the religiosity scale and work stress scale. The population of this study are employees of PT. Surya Argolika Reksa with a total sample of 50 people. The sampling technique uses saturated sampling technique. After the data is collected, the data is analyzed using technical product moment analysis. Based on the results of this study it was found that there was a negative relationship between religiosity and work stress with a value (r) of -.512 and a significant value of 0.000 (P <0.01). The effective contribution of religiosity to employee work stress is 26.2%. This shows that the higher the religiosity values can reduce the work  stress level of employee.